Strategies for Ensuring Customers’ Satisfaction by Business Entrepreneurs for Sustainability of Livelihood in Oyo State - Ayinde Dauda Oladeji; Popoola Balqis Olabisi; Muraina Kamilu Olanrewaju (Universitas Pendidikan Ganesha, 2024)
Customer satisfaction is one of the essential things that must be maintained. This research aims to analyze the various strategies that entrepreneurs can use to build customer satisfaction for sustainable livelihoods. This study used a descriptive survey design. The study population consisted of 3,659 managers of small and medium-sized enterprises registered with the Ministry of Commerce, Industry, and Technology. The sample of this study amounted to 783 small and medium-sized business owners who were taken through a proportional stratified sampling technique. The data collection instrument in this study was a structured questionnaire titled